The essentials of risk management - Crouhy, Michel; Galai, Dan.; Mark, Robert, PhD. (New York : McGraw-Hill, 2006)
This book provides you with a practical, non- Ivory tower approach that is necessary to implement a superior risk management programme effectively.
Includes index.
aug 27/05/13
Loans
Keywords: Risk management; Risk